A Rare Variant of Exstrophy-epispadias Complex with Superior Vesical Fistula in a Male Infant - Khemchandani, Sajni I. (Advancement and New Understanding in Medical Science Vol. 9, 2024)
We report a rare variant of exstrophy-epispadias complex, a duplicate abdominal urinary bladder communicating with exstrophy bladder via a fistula. On presentation, the mucosal patch on abdomen appeared to be a case of classical bladder exstrophy associated with diastasis of the pubis and rectus muscles, a low-lying umbilicus and a form of epispadias. On careful examination, infant’s phallus appeared normal with dorsal chordee and normal external urethral meatus. Micturating cysto-urethrogram was done, which elicited a rare anomaly; duplicate bladder exstrophy.